Implementation of Legislative Duties of DPRD Members in Bulukumba Regency for the 2014-2019 period - Andi Cipta Diary Herzu (Universitas Negeri Makassar, 2023)
This research discusses the implementation of legislative tasks by members of the Regional People's Representative Council (DPRD) of Bulukumba Regency for the period 2014-2019, using Edward III's theory that includes the variables of communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of legislative tasks has been relatively good or effective. The policy implementation at the Bulukumba Regency DPRD has achieved its objectives and targets with smooth routines and no major issues. Effective communication characterized by transmission, clarity, and consistency supports the successful implementation of policies. Competent human resources, sufficient financial resources, and effective resource management, including time, are vital factors in the effectiveness of policy implementation. The disposition of implementers, involving commitment, honesty, and democratic values, also plays a significant role in policy execution. The bureaucratic structure, including Standard Operating Procedures (SOPs) governing workflow and policy implementation, facilitates effective legislative tasks. Overall, it can be concluded that the implementation of legislative tasks by members of the Bulukumba Regency DPRD for the period 2014-2019 has been relatively successful.